Total body water dynamics estimated with bioelectrical impedance vector analysis and B-type natriuretic peptide after exposure to hypobaric hypoxia: A field study - Strapazzon, G.; Pun, M.; Dal Cappello, T.; Procter, E.; Lochner, P.; Brugger, H.; Piccoli, A. (High Altitude Medicine & Biology, 2017)
The relationship between total body water (TBW) dynamics and N-terminal pro-B-type natriuretic peptide (NT-proBNP), a stable metabolite of B-type natriuretic peptide, during acute high altitude exposure is not known. To investigate this, we transported 19 healthy lowland subjects to 3830 m with a helicopter after baseline measurements (262 m). The physiological measurements and clinical assessments were taken at 9, 24, 48, and 72 hours and on the eighth day of altitude exposure. A bioelectrical impedance vector analysis (BIVA) from height corrected Resistance-Reactance (R-Xc graph) was used to estimate TBW status. NT-proBNP was measured from venous blood samples. The changes in impedance vector were lengthened at 9 (p = 0.011), 48 (p = 0.033), and 72 hours (p = 0.015) indicating dehydration compared to baseline. However, there was no dehydration at 24 hours (p > 0.05) from the baseline and the subjects trended to get euhydrated from 9 to 24 hours (p = 0.097). The maximum percent changes in vector length from the baseline were within 10%-15%. There was a significant increase of ln(NT-proBNP) after ascent with a peak at 24 hours, although similarly to BIVA values, ln(NT-proBNP) returned to baseline after 8 days of altitude exposure. The changes in impedance vector length were not correlated with the changes in ln(NT-proBNP) (r = -0.101, p = 0.656). In conclusion, the dehydration at high altitude as reflected by 10%-15% vector lengthening falls within "appropriate dehydration" in healthy lowland subjects. NT-proBNP does not simply reflect the TBW status during acute high altitude exposure and needs further investigation.